Fabrication of palladium/platinum core-shell nanoparticles by electroless metal plating - Yoshio Kobayashi; Hideki Kunigami (Zaštita Materijala)
An electroless metal plating method was used to form metallic platinum (Pt) shells on metallic palladium (Pd) nanoparticles. The electroless metal plating method comprised two steps: (1) reduction of Pd ions to fabricate Pd nanoparticles and (2) deposition of Pt nuclei and the following formation of Pt shells by immersing the Pd nanoparticles in a Pt-plating solution. TEM observation revealed that the nanoparticles had a size of 5.7±1.9 nm, were composed of Pd nanoparticles as core and Pt shells. The Pd/Pt core-shell nanoparticles were immobilized electrostatically on carbon support surface-modified with poly(diallyldimethylammonium chloride) (Pd/Pt/C). Cyclic voltammetry revealed that the Pd/Pt/C exerted hydrogen adsorption/desorption, expecting the Pd/Pt/C to function as catalyst for fuel cell.